Peace Studies Edges and Innovations : Marketing Peace : Deconstructing Christian-Muslim Narratives of God, Salvation and Terrorism (1).: Edges and Innovations : Marketing Peace : Deconstructing Christian-Muslim Narratives of God, Salvation and Terrorism (1). (2017-09-01 00:00:000) - Unknown
No abstract available